2019
DOI: 10.1016/j.celrep.2019.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Proteomic and Phosphoproteomic Responses to Signaling Network Perturbations Reveals Functional Pathway Organizations in Yeast

Abstract: SUMMARY Governance of protein phosphorylation by kinases and phosphatases constitutes an essential regulatory network in eukaryotic cells. Network dysregulation leads to severe consequences and is often a key factor in disease pathogenesis. Previous studies revealed multiple roles for protein phosphorylation and pathway structures in cellular functions from different perspectives. We seek to understand the roles of kinases and phosphatases from a protein homeostasis point of view. Using a streamline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 58 publications
2
57
1
Order By: Relevance
“…4 C ). Notably, two phosphorylation sites previously reported on Set1p ( 35 ), at threonine 1001 and threonine 1006, are situated at its interface with Swd1p ( Fig. 4 C , inset ).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…4 C ). Notably, two phosphorylation sites previously reported on Set1p ( 35 ), at threonine 1001 and threonine 1006, are situated at its interface with Swd1p ( Fig. 4 C , inset ).…”
Section: Resultsmentioning
confidence: 60%
“…A comprehensive catalog of modification types and sites on an enzyme is requisite to understanding its post-translational regulation. Although several enrichment-based proteomic studies have identified many PTMs on histone MTases and DMases in S. cerevisiae ( 33 , 34 , 35 , 36 , 37 , 38 ), there has been no systematic characterization of any specific methylation enzymes carried out to date. To this end, we homologously overexpressed and purified all yeast histone MTases and DMases and performed a combinatorial mass spectrometric pipeline ( 39 ) to comprehensively identify high-confidence PTM sites of various types.…”
mentioning
confidence: 99%
“…Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway enrichment analyses were further performed based on Fisher's exact test to map the DEPs 38,39 . The protein‐protein interaction (PPI) networks were predicted using STRING (https://string-db.org) and Cytoscape software 40 …”
Section: Methodsmentioning
confidence: 99%
“…38,39 The protein-protein interaction (PPI) networks were predicted using STRING (https://string-db.org) and Cytoscape software. 40…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Phosphoproteomics, the systematic and unbiased mapping of phosphorylation events, is achieved mainly using mass spectrometry (MS)-based approaches. Both instrumentation and bioinformatic tools applied for phosphopeptide identification have been continuously evolving 15 17 , culminating in large phosphoproteomic datasets in recent years 18 24 . In addition to in depth coverage of the phosphoproteome, comprehensive mapping of kinase-mediated signaling also requires quantitative analysis of each phosphopeptide or phosphorylation site to monitor its abundance in conditions of active kinase compared to conditions in which the kinase of interest is chemically and/or genetically ablated 11 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%